2009
DOI: 10.1261/rna.1776409
|View full text |Cite
|
Sign up to set email alerts
|

AtnMat2, a nuclear-encoded maturase required for splicing of group-II introns in Arabidopsis mitochondria

Abstract: Mitochondria (mt) in plants house about 20 group-II introns, which lie within protein-coding genes required in both organellar genome expression and respiration activities. While in nonplant systems the splicing of group-II introns is mediated by proteins encoded within the introns themselves (known as ''maturases''), only a single maturase ORF (matR) has retained in the mitochondrial genomes in plants; however, its putative role(s) in the splicing of organellar introns is yet to be established. Clues to other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
227
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(238 citation statements)
references
References 85 publications
11
227
0
Order By: Relevance
“…This phenomenon has been reported for other mutants, such as otp43 (Falcon de Longevialle et al, 2007), bir6 (Koprivova et al, 2010), mtsf1 (Haïli et al, 2013), nMat1 (Keren et al, 2012), nMat2 (Keren et al, 2009), nMat4 (Cohen et al, 2014), mcsf1 (Zmudjak et al, 2013), and indh (Wydro et al, 2013), as well as the Nicotiana sylvestris mutant cms2 (Gutierres et al, 1997) and the maize (Zea mays) nonchromosomal stripe1 (Karpova and Newton, 1999). The molecular defect in tang2 is much stronger than that of otp439, and this is reflected by the quantity of the assembled complex I in the mutants, which is very likely the reason behind the discrepancy between their phenotypes.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…This phenomenon has been reported for other mutants, such as otp43 (Falcon de Longevialle et al, 2007), bir6 (Koprivova et al, 2010), mtsf1 (Haïli et al, 2013), nMat1 (Keren et al, 2012), nMat2 (Keren et al, 2009), nMat4 (Cohen et al, 2014), mcsf1 (Zmudjak et al, 2013), and indh (Wydro et al, 2013), as well as the Nicotiana sylvestris mutant cms2 (Gutierres et al, 1997) and the maize (Zea mays) nonchromosomal stripe1 (Karpova and Newton, 1999). The molecular defect in tang2 is much stronger than that of otp439, and this is reflected by the quantity of the assembled complex I in the mutants, which is very likely the reason behind the discrepancy between their phenotypes.…”
Section: Discussionsupporting
confidence: 76%
“…and M. polymorpha also contain several group I introns, the vast majority of the introns in flowering plants (with the exception of the cox1 intron in some species) belong to group II, with 23 in Arabidopsis and rice (Oryza sativa; Bonen, 2008). These introns seem to have lost their self-splicing ability, thus necessitating the help of maturases such as the nuclearly encoded nMAT1, nMAT2, nMAT3, and nMAT4 and possibly the mitochondrial MatR, whose function is still elusive (Keren et al, 2009(Keren et al, , 2012Brown et al, 2014;Cohen et al, 2014). Plant mitochondrial DNA is renowned for its high recombination rates and its ability to integrate foreign DNA sequences, explaining the difficulty of retracing the evolutionary story of group II introns (Bonen, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S5). Notably, a number of recent studies have also confirmed the observed localization for four of these proteins, At5g46920 (Keren et al, 2009), At1g80270 (Doniwa et al, 2010), At5g60960 (Hammani et al, 2011), and At4g36040 (Chen et al, 2010).…”
Section: Confirming the Organellar Location Of Proteins With Gs Exprementioning
confidence: 64%
“…To date, there has been little information regarding their changes to explain regulation under different environments because PPR genes are expressed at low levels 47 . Furthermore, group II intron splicing factors besides PPR proteins have been found: MRS2, a homologue of the yeast splicing factor 68,69 , maturases, Marchantia or yeast group II intronic ORF homologs in higher plants 31,32,53,55 , PMH2, a DEAD-box protein 33 , and so on. Information on these genes will help develop environmental tolerances of crops.…”
Section: Perspective Of a Plant Organelle Biological Study Concerninmentioning
confidence: 99%